The prisoner [large type] - Paris, B. A. (Wheeler Publishing, a part of Gale, a Cengage Company, 2022)
"With Behind Closed Doors, New York Times bestselling author B.A. Paris took the psychological thriller to shocking new heights. Now she'll hold you captive with THE PRISONER-a stunning new thriller about one woman wed into a family with deadly intentions. Amelie has always been a survivor, from losing her parents as a child in Paris to making it on her own in London. As she builds a life for herself, she is swept up into a glamorous lifestyle where she married the handsome billionaire Jed Hawthorne. But then, Amelie wakes up in a pitch-black room, not knowing where she is. Why has she been taken? Who are her mysterious captors? And why does she soon feel safer here, imprisoned, than she had begun to feel with her husband Jed? In the vein of Behind Closed Doors and The Therapist, multimillion-copy bestseller B.A. Paris is back with a gripping new suspense novel"--